Achieving LDL cholesterol target levels <1.81 mmol/L may provide extra cardiovascular protection in patients at high risk: Exploratory analysis of the Standard Versus Intensive Statin Therapy for Patients with Hypercholesterolaemia and Diabetic Retinopathy study. Issue 4 (6th December 2018) - Itoh, Hiroshi; Komuro, Issei; Takeuchi, Masahiro; Akasaka, Takashi; Daida, Hiroyuki; Egashira, Yoshiki; Fujita, Hideo; Higaki, Jitsuo; Hirata, Ken‐ichi; Ishibashi, Shun; Isshiki, Takaaki; Ito, Sadayoshi; et al.
Abstract : Aims: To assess the benefits of intensive statin therapy on reducing cardiovascular (CV) events in patients with type 2 diabetes complicated with hyperlipidaemia and retinopathy in a primary prevention setting in Japan. In the intension‐to‐treat population, intensive therapy [targeting LDL cholesterol <1.81 mmol/L (<70 mg/dL)] was no more effective than standard therapy [LDL cholesterol ≥2.59 to <3.10 mmol/L (≥100 to <120 mg/dL)]; however, after 3 years, the intergroup difference in LDL cholesterol was only 0.72 mmol/L (27.7 mg/dL), and targeted levels were achieved in <50% of patients. We hypothesized that the intergroup difference in CV events would have been statistically significant if more patients had been successfully treated to target. Materials and Methods: This exploratory post hoc analysis focused on intergroup data from patients who achieved their target LDL cholesterol levels. The primary endpoint was the composite incidence of CV events. A Cox proportional hazards model was used to estimate hazard ratios (HRs) for incidence of the primary endpoint in patients who achieved target LDL cholesterol levels in each group. Results: Data were analysed from 1909 patients (intensive: 703; standard: 1206) who achieved target LDL cholesterol levels. LDL cholesterol at 36 months was 1.54 ± 0.30 mmol/L (59.7 ± 11.6 mg/dL) in the intensive group and 2.77 ± 0.46 mmol/L (107.1 ± 17.8 mg/dL) in the standard group ( P < 0.05). After adjusting for baseline prognostic factors, the composite incidence of CV events or deaths associated with CV events was significantly lower in the intensive than the standard group (HR 0.48; 95% confidence interval 0.28‐0.82; P = 0.007). Conclusions: This post hoc analysis suggests that achieving LDL cholesterol target levels <1.81 mmol/L may more effectively reduce CV events than achieving target levels ≥2.59 to <3.10 mmol/L in patients with hypercholesterolaemia and diabetic retinopathy.